Fragmentation and vulnerability in Anne Enright’s The green road (2015): Collateral casualties of the Celtic Tiger in Ireland - Barros-del Rio, Maria Amor (International Journal of English Studies, 2018)
This article explores the representation of family and individuals in Anne Enright’s novel The Green Road (2015) by engaging with Zygmunt Bauman’s sociological category of “liquid modernity” (2000). In The Green Road, Enright uses a recurrent topic, a family gathering, to observe the multiple forms in which particular experiences seem to have suffered a process of fragmentation during the Celtic Tiger period. A comprehensive analysis of the form and plot of the novel exposes the ideological contradictions inherent in the once hegemonic notion of Irish family and brings attention to the different forms of individual vulnerability for which Celtic Tiger Ireland has no answer.